GAMBARAN WORK-LIFE BALANCE PADA PROFESI PERAWAT SELAMA MASA PANDEMI COVID-19, DI RUMAH SAKIT DI JABODETABEK - Samuel Nugraha; Rini Sugiarti; Fendy Suhariadi (KOLONI, 2022)
At this time, the world is still facing a global pandemic, and one of them is Indonesia. It’s causes of the global pandemic was caused by the virus disease 2019, or Covid-19. The impact of the global pandemic in the world, has resulted in a high case fatality rate. Nurses have an important role in efforts to treat patients who have infected COVID-19 virus. The soaring number of infection cases makes nurses have to work extra in an effort to treat patients optimally. In addition to serving as nurses, they also serve as heads of families who are responsible for their own families. These two roles demand a balanced performance. A balance between work and personal life is needed so that individuals can balance work with other activities outside of work. The purpose of this study was to describe the work-life balance of nurses during the COVID-19 pandemic in hospitals in Jabodetabek. This research is expected to be able to contribute to the science of psychology, especially those related to work-life balance in the context of health workers. This study used a qualitative approach with purposive sampling technique, involving 2 nurses aged 35 years old and 37 years old. Data were obtained using in-depth interviews (in-depth interviews). The results showed that of the four dimensions of work-life balance, 2 of them indicated the achievement of balance. The unbalanced dimensions are WIPL (work Interference with Personal Life) and PLIW (Personal Life Interference with Work). Thus, the subject has not been optimal in balancing his work life with his personal life due to the type of work as a nurse during this pandemic who must be prepared when receiving an emergency call. This subject tends to be difficult to divide time proportionally between work life and personal life. Keyword: work-life balance, qualitative, nurse, pandemic COVID-19